Foreign Direct Investment in India - Ladha, Ritesh (2009)
Over the years India has transformed to become one of the most favourable destinations for FDI. Since the reforms of 1991, the flow of FDI in India has been increasing which has led to the development of the Indian economy as a whole and has successfully integrated with the world economy. The purpose of this dissertation is to see the trend of the flow of FDI to India, further highlighting the countries which have found India as a favourable FDI destination, the trend of their investment and then the trend of FDI inflows in various sectors have been studied. In the literature review we talk about the different theories of FDI, further we introduce how India’s economy achieved a liberal economy’s status and finally the empirical evidence has been cited.